Pengaruh Temperatur Operasi Terhadap Fuel Convertion Rate Insinerator Fluidized Bed Dengan Bed Material Pasir Besi - Migra, Zony; Winaya, I Nyoman Suprapta; Suryawan, I Gede Putu Agus (Teknik Desain Mekanika, 2022)
Abstractt Medical waste has recently increased in number due to the handling of the Coronavirus Disease pandemic has become a serious environmental issue, and proper waste management methods are needed. The best technology in processing and minimizing the amount of waste flow at this time is using incinerator technology. High temperatures combustion in incinerator may reduce volume, and can also decrease the medical waste infectious properties. The reactor that used is a fluidized bed reactor with magnetite as bed material to reduce emissions that are considered dangerous from the combustion of medical waste. Applying the experimental study method, this research is used for determine the effect of operating temperature on the fuel convertion rate of the incinerator. The operating temperature variations used are 500°C; 550°C; 600°C; and 650°C. The result of this research is that the operating temperature of 650°C has the highest FCR of 1.655 kg/h. This shows that the higher the operating temperature, the better the combustion that occurs in the incineration process. Keywords: Incinerator, Medical Waste, Magnetite, Fuel Convertion Rate, Temperature.